KELAS ASYIK DENGAN PERMAINAN KLASIK: METODE INOVATIF UNTUK PEMBELAJARAN BAHASA INGGRIS INTERAKTIF DI SDN 11 DAUH PURI - Ni Made Verayanti Utami; Ni Wayan Suastini; Ni Luh Vira Nitya Rini; Anak Agung Made Indrawati (LOKATARA SARASWATI, 2024)
This community service aims to increase the effectiveness and engagement of students in learning English through the application of classic game methods. The scope of the service covers English teaching in grades 1 to 6 of SDN 11 Dauh Puri with a focus on the use of classic games, such as "Telephone" and "Hangman." The methods used includes planning and implementing classic game-based learning sessions, followed by evaluation of student learning outcomes. These games were chosen because they can create a fun and interactive learning atmosphere, encouraging students to actively participate in the learning process. The results of this program show a significant increase in students' interest and engagement during English lessons. Students showed greater enthusiasm and improved language skills after participating in the classic game sessions. The evaluation also revealed that this method helps students in understanding new vocabulary and language concepts in a more fun way. The conclusion of this article is that classical games can be an effective method in creating an interactive and fun learning atmosphere, as well as improving English learning outcomes at the primary school level. The integration of classical games in learning not only improves students' language skills but also makes the learning process more interesting and motivating.